FOREWORD FROM HANDLING EDITOR - 6TH EDITION - Sodri, Ahyahudin (UI Scholars Hub, 2021)
We are delighted to present the 6th edition of JESSD, published in July 2021. We have selected seven of the best articles from Indonesia, Japan and Brazil for this edition that related with topic of Environmental Science and Sustainable Development.